Addressing Criminality in Childhood: Is Responsivity the Central Issue?. (November 2013) - Nee, Claire; Ellis, Tom; Morris, Paul; Wilson, Amy
The responsivity principle is the third element of the now well-established risk–need–responsivity (RNR) model of offender rehabilitation. Accruing evidence suggests it is often sacrificed in intervention programs. We aim to demonstrate the central importance of this principle when designing offender interventions by describing the results of a successful, highly responsive intervention for very young children (aged 7 upward) who have offended. A small slice of the offending population as a whole, child offenders are nevertheless tomorrow's serious, violent, and prolific lawbreakers, yet little is understood about what reduces their risk. Recent developments on responsivity are reviewed, before presenting the evaluation indicating significant and sustained drops in risk of recidivism. In-program factors such as the nature and dosage of interventions are examined, alongside outcome data. The article discusses how RNR and other models might apply to this particularly young and underresearched age group.